2014
DOI: 10.1007/s00702-014-1207-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age, diagnosis, and their interaction on vertex-based measures of cortical thickness and surface area in autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is a lifelong neurodevelopmental condition that is accompanied by an atypical development of brain maturation. So far, brain development has mainly been studied during early childhood in ASD, and using measures of total or lobular brain volume. However, cortical volumetric measures are a product of two distinct biological neuroanatomical features, cortical thickness, and surface area, which most likely also have different neurodevelopmental trajectories in ASD. Here, we therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 53 publications
2
58
1
1
Order By: Relevance
“…Shaywitz, et al, 2007; Yeatman, et al, 2012). These interactions further suggest that, similar to other neurodevelopmental disorders such as attention deficit hyperactivity disorder and autism (Ecker, et al, 2014; Shaw, et al, 2007), dyslexia might also be characterized by atypical developmental trajectory of specific brain areas.…”
Section: Discussionmentioning
confidence: 81%
“…Shaywitz, et al, 2007; Yeatman, et al, 2012). These interactions further suggest that, similar to other neurodevelopmental disorders such as attention deficit hyperactivity disorder and autism (Ecker, et al, 2014; Shaw, et al, 2007), dyslexia might also be characterized by atypical developmental trajectory of specific brain areas.…”
Section: Discussionmentioning
confidence: 81%
“…Cortical thickness is a rich attribute that has the potential to help identify early postnatal neurodevelopmental disorders (Ecker et al, 2014; Querbes et al, 2009; Singh et al, 2008). To overcome the need of additional MRI scans later on for individual assessment of cortical thickness changes, we proposed a generic prediction framework for any cortical attributes from single or multiple time point(s).…”
Section: Discussionmentioning
confidence: 99%
“…4 Additionally, while autism spectrum disorders present symptoms throughout the lifespan, they typically first present very early in life and are associated with altered developmental trajectories of brain structure, 1820 which may furthermore interact with key features of the diagnosis (eg, as indicated by IQ). 18,19 In light of this, and the fact that the 10 VBM studies we identified of adults with autism spectrum disorders largely did not address this heterogeneity, we opted to exclude autism to maximize interpretability of our results. Studies in which some patients were younger than age 18 years were included so that for the diagnoses selected all available studies were included.…”
Section: Methodsmentioning
confidence: 99%